Analysis of Rasulullah's Marketing Mix in Contemporary Business - Sri Wahyuni Safitri AR; Khusnul Khowatim; Umi Julaihah (MONETARIUM: Journal of Economics Business and Management, 2025)
Sharia marketing directs the creation, offering and changing of value from the initiator to the stakeholders in the process in accordance with the principles of muamalah (business) in Islam. Its function is no longer deviation and the ethical values ​​of morality (akhlakul karimah) are a blessing. This research aims to determine the marketing mix variables ala Rasulullah, namely the 5 variables Product, Price, Place, Promotion and Patience which influence contemporary business today. This type of research is a type of research that uses qualitative analysis through library research and related journals, using disclosure analysis and then interpreting it in certain circumstances. Presentation without using statistics. The aim is to analyze the Prophet's marketing mix in contemporary business. Sharia marketing or Rasulullah-style marketing directs the creation, offering and changing of value from the initiator to the stakeholders, which in the process is in accordance with the principles of muamalah (business) in Islam. Its function is no longer deviation and the ethical values ​​of morality (akhlakul karimah) are a blessing.